2018
DOI: 10.5944/reop.vol.28.num.3.2017.21615
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de un modelo social-cognitivo de la elección de la carrera desde la tipología de Holland en estudiantes de la escuela secundaria/Testing social cognitive career choice model across Holland types in high school students

Abstract: RESUMENLa teoría social cognitiva de la carrera (SCCT; Lent, Brown & Hackett, 1994) se formuló originalmente con la finalidad de integrar diferentes modelos y constructos para lograr una comprensión más profunda de los mecanismos que regulan el desarrollo de los intereses vocacionales, la elección de la carrera y el rendimiento académico (Lent, et al., 1994, 2000). En la presente investigación se evalúa un modelo de intención de elección de carrera derivado de la SCCT. La muestra estuvo conformada por alum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
7
0
2
Order By: Relevance
“…Conversely, the present results indicated that the latent traits that better explained the items consisted of the RIASEC typology rather than the SSs. These results are consistent with a previous study in Argentina by Cupani, Azpilicueta, and Sialle (2017). This previous study investigated the explanatory power of the sources of self-efficacy in career decision-making and found that the percentage of variance that was explained was stable throughout the different RIASEC typologies and higher for the realistic, investigative, and artistic types.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, the present results indicated that the latent traits that better explained the items consisted of the RIASEC typology rather than the SSs. These results are consistent with a previous study in Argentina by Cupani, Azpilicueta, and Sialle (2017). This previous study investigated the explanatory power of the sources of self-efficacy in career decision-making and found that the percentage of variance that was explained was stable throughout the different RIASEC typologies and higher for the realistic, investigative, and artistic types.…”
Section: Discussionsupporting
confidence: 91%
“…According to SCCT, the development of career goals (career choice process) is conceived as a sequence of interests, intentions, and behaviors that are presented as occupational choices where career intentions arise from the previous training of vocational interests [72]. The interests stimulate the career intentions or choice of goals (the plans of dedicating oneself to a certain activity and to achieve a certain result in the future), which increase the probability of making a career choice behavior (specific actions that mark the entry of the individual into an academic or professional line of work) [74,75]. From this standpoint, interests are defined as early patterns of attraction towards occupational-related activities [76], career intentions or set-choice goals are plans to dedicate oneself to a certain activity, and career choice behaviors are specific actions that mark the entry of the individual into a professional career [36].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…According to SCCT, the development of career goals (career choice process) is conceived as a sequence of interests, intentions, and behaviors that are presented as occupational choices where career intentions arise from the previous training of vocational interests [75]. The interests stimulate the career intentions or choice of goals (the plans of dedicating oneself to a certain activity and to achieve a certain result in the future), which increase the probability of making a career choice behavior (specific actions that mark the entry of the individual into an academic or professional line of work) [77,78]. From this standpoint, interests are defined as early patterns of attraction towards occupational-related activities [79], career intentions or set-choice goals are plans to dedicate oneself to a certain activity, and career choice behaviors are specific actions that mark the entry of the individual into a professional career [47].…”
Section: Theoretical Backgroundmentioning
confidence: 99%